Wielding a double-edged sword: viruses exploit host DNA repair systems to facilitate replication while bypassing immune activation - Saladino, Nicholas; Salamango, Daniel J. (Frontiers in Virology, 2024)
Viruses are obligate intracellular pathogens that hijack a myriad of host cell processes to facilitate replication and suppress host antiviral defenses. In its essence, a virus is a segment of foreign nucleic acid that engages host cell machinery to drive viral genome replication, gene transcription, and protein synthesis to generate progeny virions. Because of this, host organisms have developed sophisticated detection systems that activate antiviral defenses following recognition of aberrant nucleic acids. For example, recognition of viral nucleic acids by host DNA repair proteins results in compromised viral genome integrity, induction of antiviral inflammatory programs, cell cycle arrest, and apoptosis. Unsurprisingly, diverse viral families have evolved multiple strategies that finetune host DNA repair responses to suppress activation of antiviral defenses while simultaneously hijacking DNA repair proteins to facilitate virus replication. This review summarizes common molecular strategies viruses deploy to exploit host DNA repair mechanisms.